2022
DOI: 10.1097/mpg.0000000000003552
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Eosinophilic Esophagitis in a Black and Non-Black Pediatric Cohort

Abstract: Objectives: To compare presenting symptoms, comorbidities, disease, and treatment characteristics of a black pediatric eosinophilic esophagitis (EoE) group to a non-black pediatric EoE group. Methods: A retrospective chart review consisting of pediatric patients diagnosed with EoE between the years of 2010 and 2018 at a single urban pediatric hospital system comprising 143 black pediatric patients compared with 142 non-black pediatric patients with similar distribution of age and sex. Results: Both groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…31 There was no statistically significant difference between the groups in obtaining remission with available treatments, although the black group exhibited greater rates of no adherence to medical treatments. 30,31 Currently it is recognized that the incidence of EoE is increasing in the Western world and is less prevalent in Asia, despite both populations sharing similar endoscopic and clinical characteristics, and that there may be differences in clinical presentation amongst different ethnicities. 32 Sperry et al 28 found that whites with EoE were older than blacks, less likely to present with failure-tothrive, and more likely to have esophageal rings on upper endoscopy.…”
Section: Racial and Ethnic Differencesmentioning
confidence: 83%
See 2 more Smart Citations
“…31 There was no statistically significant difference between the groups in obtaining remission with available treatments, although the black group exhibited greater rates of no adherence to medical treatments. 30,31 Currently it is recognized that the incidence of EoE is increasing in the Western world and is less prevalent in Asia, despite both populations sharing similar endoscopic and clinical characteristics, and that there may be differences in clinical presentation amongst different ethnicities. 32 Sperry et al 28 found that whites with EoE were older than blacks, less likely to present with failure-tothrive, and more likely to have esophageal rings on upper endoscopy.…”
Section: Racial and Ethnic Differencesmentioning
confidence: 83%
“…31 There was no statistically significant difference between the groups in obtaining remission with available treatments, although the black group exhibited greater rates of no adherence to medical treatments. 30,31…”
Section: Racial and Ethnic Differencesmentioning
confidence: 83%
See 1 more Smart Citation
“…A recent cross-sectional study demonstrated adherence of 76.2% in adolescents and 88.6% in younger children, 12 and a single center review found 33.6% nonadherence rates in a Black cohort versus 10.9% in the non-Black cohort. 13 Comorbid atopic disease may be an additional reason to consider dupilumab, although its cost may prevent it from being first-line therapies for diseases that can be well-controlled.…”
Section: Indications For Dupilumabmentioning
confidence: 99%
“…A retrospective chart review of pediatric patients diagnosed with EoE between 2010 and 2018 comprising 143 Black patients compared with 142 non-Black patients with similar distribution of age and sex was conducted (20). Both groups were majority male, and the median age of diagnosis in Black and non-Black group was 5.1 and 6.7 years old, respectively.…”
Section: Eosinophilic Gastrointestinal Diseasesmentioning
confidence: 99%